Akurep air sell & services / Muhammad Danieal Hadi Samion ... [et al.] - Samion, Muhammad Danieal Hadi; Mohd Yusoff, Mohd Zulkarnain; Muhammad, Muhammad Haziq; Mohd Ridza, Mohamad Rafiq; Husin, Mohamad Haziq; Mazni, Mohamad Afiq (2016)
In the modem world, one of the most important and necessary items of use is a computer or a laptop. It plays a vital role in his every day work and is of great help. Charles Babbage has given the best gift possible to the humans by inventing a computer. Laptop computers can suffice every single need of today. We can work, surf the internet, playing games and lots more. It increases the efficiency of the humans resulting in great and optimum utilization of time and energy. One more important aspect of laptops and computers is that people can bank online, shop online, buy or sell online and work online too. So, this invention has revolutionized our economy in a positive way. It is due to this reason that computers have reached every nook and comer of the world and is in great use.